2019
DOI: 10.1029/2018gl081334
|View full text |Cite
|
Sign up to set email alerts
|

Skilful Seasonal Prediction of Ocean Surface Waves in the Atlantic Ocean

Abstract: Ocean surface wave height in the Atlantic Ocean is strongly influenced by the North Atlantic Oscillation (NAO). Here we demonstrate for the first time a skilful seasonal forecast for wave height in the Atlantic Ocean, produced by a seasonal prediction system with an enhanced prediction skill of winter NAO. The improved seasonal prediction skill of the wave height reaches 0.8 in major parts of the North Atlantic. Prediction skill in the Central and South Atlantic is significantly improved due to swell propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For example, Wang et al (2017) used multiple linear regression of key discriminant variables (sea-ice concentration, stratospheric circulation and sea-surface temperature) and obtained forecast skill (r) of 0.69-0.71. Combined, these advances suggest that skillful prediction of seasonal and decadal coastal vulnerability may be possible (Colman et al, 2011;Dobrynin et al, 2019), where forecasts of climate indices may provide a valuable tool for managing risk to society due to extreme winter-wave events, wave directional variability and corresponding geomorphological change at the coast.…”
mentioning
confidence: 99%
“…For example, Wang et al (2017) used multiple linear regression of key discriminant variables (sea-ice concentration, stratospheric circulation and sea-surface temperature) and obtained forecast skill (r) of 0.69-0.71. Combined, these advances suggest that skillful prediction of seasonal and decadal coastal vulnerability may be possible (Colman et al, 2011;Dobrynin et al, 2019), where forecasts of climate indices may provide a valuable tool for managing risk to society due to extreme winter-wave events, wave directional variability and corresponding geomorphological change at the coast.…”
mentioning
confidence: 99%
“…Other studies [24] have also shown that, over the years, episodes of extreme waves have become more frequent in the Atlantic Ocean, and therefore studies such as ours are very necessary when designing a maritime infrastructure. A study of wave heights in the Atlantic Ocean [25], covering the period from 1982 to 2017, studies the seasonal prediction in all areas of the Atlantic. In its conclusions it states that, especially in the mid-Atlantic ridge (where the Canary Islands are located), the prediction of heights has improved greatly over the years and that the data currently provided are very accurate for marine designs.…”
Section: Resultsmentioning
confidence: 99%
“…The study area is located on the west coast of Ireland (9.26 • -10.79 • W, 52.33 • -53.26 • N), as is shown for the Atlantic in Figure 1. It is located in the westerlies and ocean current movements are affected by the North Atlantic Oscillation and low-pressure system [27,28]. Figure 1b shows that the bathymetry in the study area ranges from 0-140 m, and the isobaths nearshore are roughly parallel to the coastline.…”
Section: Hfr Systemmentioning
confidence: 97%
“…Compared to traditional current measuring instruments, it has several advantages: its high spatial and temporal resolution and wide area of coverage, and that it is on an all-weather system. HFR senses fields of sea surface currents, waves, and sea surface winds using Bragg scattering and Doppler frequency shift effects produced by the interactions between high-frequency radio waves and the sea surface [27,29].…”
Section: Hfr Systemmentioning
confidence: 99%